The role of fine-needle aspiration biopsy (FNAB) in Warthin tumour diagnosis and management - Jechova, Alzbeta; Kuchar, Martin; Novak, Stepan; Koucky, Vladimir; Dostalova, Lucie; Zabrodsky, Michal; Kalfert, David; Plzak, Jan (European archives of oto-rhino-laryngology, 2019)
PURPOSE: Warthin tumour (WT) is the second most common benign tumour of the parotid gland. The aim of this study was to assess the value of the FNAB in the diagnosis and treatment decision in patients with WT. MATERIALS AND METHODS: We performed a retrospective study of patients treated for parotid gland mass between 2006 and 2016. Patients who underwent the surgery with preoperative FNAB were considered. The first group was comprised of patients with preoperative FNAB showing WT and the second group was formed by patients with definitive histology of WT. RESULTS: 216 patients had FNAB with the result of WT and underwent surgery (98 women-45.4% and 118 men-54.6%). The definitive histology corresponded with the preoperative diagnosis in 201 cases (93.1%). The other way round, 222 patients were operated with definitive histology showing WT and we correlated this finding with preoperative FNAB. The result of FNAB corresponded with definitive histology of WT in 201 cases (90.5%). Counted sensitivity and specificity of the ultrasound-guided FNAB for the diagnosis of WT were, respectively: 96.63% (CI 93.19-98.64%) and 96.21 (CI 93.83-97.86%). The accuracy of this method was 96.36% (CI 94.54-97.70%). CONCLUSION: Ultrasound-guided FNAB is a safe, accurate and important method in WT diagnosis. The therapeutic approach can be chosen based on FNAB results correlated with other clinical findings. We propose that when WT is suspected, follow-up or enucleation of the tumour are appropriate treatments. Patient preferences should be also considered.
Keywords: ultrazvukem navigovaná biopsie; senzitivita a specificita; intervenční ultrasonografie; Sensitivity and Specificity; Humans; Parotid Neoplasms; lidé středního věku; výběr pacientů; Patient Selection; Female; Image-Guided Biopsy; lidé; parotis; Ultrasonography, Interventional; Parotid Gland; ženské pohlaví; Male; Middle Aged; Retrospective Studies; Adenolymphoma; adenolymfom; Biopsy, Fine-Needle; retrospektivní studie; mužské pohlaví; tenkojehlová biopsie; nádory příušní žlázy